Investigation on asphaltene precipitation during carbon dioxide flooding for oil recovery - Abdalla A. M., Ben Ali (2016)
Asphaltene precipitation is one of the serious problems during the secondary and tertiary oil recovery in light oil reservoirs using carbon dioxide injection. Asphaltene precipitation leads to significant problem in production system such as wellbore plugging, permeability reduction and porosity alteration. In this work, light crude oil was chosen to predict the effect of carbon dioxide injection and its interaction with oil. Saturate aromatic, resin and asphaltene (SARA) analysis was conducted to know the propensity of the light crude oil to precipitate. Later, the laboratory study was conducted to analyse the behaviour of asphaltene and carbon dioxide with different gas oil ratios (GOR). Different pressure volume temperature (PVT) experiments were conducted to know the asphaltene precipitation behaviour. The results from the PVT test showed that asphaltene precipitation was found significant at GOR 310 scf/st and the bubble point pressure of 2100 Psig. Dynamic core flooding study with various carbon dioxide concentrations and flow rates were conducted to measure asphaltene precipitation induced by carbon dioxide. Before running the core flooding, the minimum miscibility pressure was determined and it was found to be 1500 Psi. Three Berea sandstone cores were used as formation reservoir to determine the asphaltene precipitation and to study the effect of carbon dioxide injection. The parameters for three cores were kept constant at the pressure of 2000 Psi and temperature of 100°C while varying the injection flow rates. The three flow rates of 0.4 cc/min, 0.6 cc/min and 0.8 cc/min were set for three core flooding runs, i.e. Core 1, 2 and 3 respectively. As the pore volume of gas injected increased, there was a decreased in the asphaltene content in the recovered oil and thus the amount of asphaltene recovered in the core is increased. At pore volume 1.00 cc, the asphaltene precipitation from the dynamic core flooding tests for Core 1, 2 and 3 were found to be 0.13% wt, 0.18% wt, and 0.19% wt respectively. From the study, it was found that at higher pore volume of gas injected, it will lead to more asphaltene precipitation in the core and lesser amount of asphaltene inside the oil recovered. It can be concluded that high injection of pore volume fluid in the sample core can change the resin, asphaltene ratio and precipitate higher amount of asphaltene particles. The injection flow rate of 0.8 cc/min showed the highest amount of asphaltene precipitated in the core.